Identification of C trisomies in human abortuses. Issue 3 (September 1975) - Boué, J; Boué, A; Deluchat, C; Perraudin, N; Yvert, F
Abstract : Fifteen cell lines initiated from embryonic tissues of abortuses with C trisomy were frozen and stored. They were thawed and karyotyped again with banding techniques. Trisomies 7, 8, 9, 10, and 12 were identified. Some characteristics of these abortuses are discussed in connection with the chromosome identifications.